The Development of Nahwu Teaching Materials Based on Mind Maps Using the ADDIE Model - Nur, Nuryanto; Rifa'i, Ahmad; Fajar, Abbas Sofwan Matlail (Universitas Islam Tribakti Lirboyo, Kediri, 2024)
The development of teaching materials is an important ability that a teacher must have, so that learning is more effective efficient, and interesting for students. One of them is Nahwu as a type of Arabic language science that must be studied by students. The purpose of writing this paper is to reveal how the development of Nahwu teaching materials based on Mind Mapping for a teacher with the ADDIE model. The analysis used is a qualitative approach with a research and development mode. In the initial stage, a descriptive method was used to prepare library data and existing contextual conditions. In this study, the model used is the ADDIE model, a structured development concept consisting of Analysis, Design, Development, Implementation, and Evaluation. The researcher's analysis found the importance of developing mind map-based Nahwu teaching materials with the ADDIE model with an instructional model through 5 stages of Analysis, Design, Development, Implementation, and Evaluation. With this ADDIE model, the ultimate goal is to make a product for the development of Nahwu teaching materials by the principles of truth and saheeh, usefulness, attracting students' interest, consistency, and the adequacy of the material developed. The author recommends the importance of developing teaching materials for a teacher professionally in attracting students' interest in learning, it is also necessary for academics to continue to develop teaching materials to produce a product that is beneficial for Arabic learners in particular.